The Relationship Between Social Support And Socioeconomic Status On Adolescent Mental Health - Andodo, Candra; Nanda Bachtiar, Nanda Bachtiar; Nurul Fatwati Fitriana, Nurul Fatawati Fitriana (PT. Nursing Genius Care, 2024)
Background: Impaired mental and emotional development contributes to increased behavioral problems in adulthood. Adolescent mental health is impacted by several factors, including social support and socioeconomics. Purpose: To see the relationship between social support and socioeconomic status on adolescent mental health Methods: This type of research used quantitative with observational approach. The population in this study were adolescents in Tegal City. Determination of the number of samples using the slovin method with the results of 375 respondents and for the sampling technique using Cluster Random Sampling technique. Results: The study revealed significant correlations of social support and mental health (p = 0.000). Significant correlations of socioeconomic support status with mental health (p = 0.000). Significant correlations of social support and socioeconomic relationships simultaneously (p = 0.000). Conclusion: The results of this study indicate that there is a significant influence of social support and socioeconomic on adolescent mental health in Tegal City.